PENGARUH KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - -, Suparyanto -; Wahyudi, Amin - (Universitas Slamet Riyadi, 2011)
ABSTRACT This study aimed to analyze the effect of: (1) organizational commitment on job satisfaction, (2) organizational commitment to employee performance, (3) job satisfaction on employee performance, (4) To analyze the indirect effect of organizational commitment on performance through job satisfaction in Statistics Grobogan. The experiment was conducted at the Central Bureau of Statistics Grobogan. The data used are primary data taken from questionnaires to the respondents. All data captured through questionnaires every variable. Classical assumption final results showed all the data of each variable multikolinearkitas pass the test, autocorrelation, heteroscedasticity, and normality test of data as many as 41 people. Data analysis tools are used with path analysis, test direct effect, and indirect effect test. Based on the results of hypothesis testing we can conclude: influence of organizational commitment on employee performance; influence of organizational commitment on job satisfaction; influence job satisfaction on employee performance; organizational commitment has a direct influence on the performance of employees through job satisfaction. Keywords: Organizational Commitment, Performance, Job Satisfaction.